Design and Simulation of Detection Algorithm for QRS Wave of ECG Signal - WANG Hai-ying; WANG Yuan-yuan; YAO Zhi-lin (Journal of Harbin University of Science and Technology)
Detection of ECG(electrocardiogram) signals is the basis of ECG analysis and diagnosis. In the analysis of ECG signals, it is very important to quickly and accurately detect QRS complexes. It is a prerequisite for calculating relevant parameters and diagnosis. Considering the poor real-time performance and high error detection rate of conventional ECG detection algorithms, this paper designs a forward and reverse bidirectional adaptive differential threshold detection algorithm, and increases the R-wave misdetection miss detection compensation algorithm. The algorithm is validated by the Massachusetts Institute of Technology’s MIT-BIH arrhythmia database, and the detection accuracy rate is over 99%. The experimental results show that the method is simple, effective, accurate and suitable for practical applications.